Disease progress and yield response in spring wheat cultivars and lines infected with Puccinia graminis f. sp. Tritici - Pretorius, Z. A (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric) -- University of Stellenbosch, 1982.